PERAN PENGAWAS DI UPT SMP NEGERI 2 BINAMU KABUPATEN JENEPONTO - Nugraini Binti Kamiluddin (LP2M IAIN Sultan Amai Gorontalo, 2025)
This research aims to describe the implementation of academic supervision by school supervisors at UPT SMP Negeri 2 Binamu. The study employed a descriptive qualitative approach with data collection techniques including interviews, observation, and documentation, involving informants such as the school supervisor, the principal, and teachers. The results of the study show that: 1. The supervisor serves as a partner for teachers in enhancing the quality of the teaching and learning process and student achievement. Teachers act as pioneers in disseminating best practices and innovations in student-centered learning, employing differentiated instruction tailored to students’ needs, interests, and learning styles, while also integrating character education, 21st-century learning, and the school literacy movement in a holistic manner. 2. Innovators at SMP Negeri 2 Binamu, including the principal and proactive teachers, play a crucial role as drivers of change and developers of creative and adaptive learning models, actively seeking new ideas and designing innovative teaching strategies that align with students’ needs and contemporary demands. 3. The supervisor acts as an educator, mentor, and educational consultant who guides and motivates, fosters a positive school climate, and encourages teachers’ professional growth as well as overall educational quality. As a mentor, the supervisor provides ongoing assistance to teachers in implementing teaching practices and guidance services, supporting students both academically and non-academically. 4. Motivators at UPT SMP Negeri 2 Binamu, often the principal or other school leaders, play a significant role in inspiring and maintaining the work spirit of all school staff so they can perform optimally and contribute fully to achieving the school’s vision and mission by providing consistent direction, support, and appreciation, ensuring that staff feel valued and motivated to improve their performance.